KINERJA SUPPLY CHAIN MANAGEMENT GLASS EEL (BENIH SIDAT) UNTUK MENUNJANG INDUSTRI PEMBESARAN SIDAT DI PALABUHANRATU - Robi Komarudin; Ronny Irawan Wahju; Tri Wiji Nurani (Bogor Agricultural University, 2020)
The utilization of glass eel (eel seeds) in the Cimandiri River Palabuhanratu has a very important role to support the supply chain for the eel culture industry. The purpose of this study was to estimate the amount of glass eel catch, describe the glass eel eel supply chain system, and measure the performance of the supply chain in eel culture. The research method uses quantitative methods through direct observation and interviews, as well as case studies of supply chain actors. The results showed that the highest catch of glass eel in 2019 was in June at an average of 14,859 grams (14.9 kg). The highest catch of glass eel occurred in the dry season (June - August), with a total catch of 21,884 grams (21.8 kg). The glass eel supply chain mechanism consists of supply chain flow pattern on the product flow, a good and transparent flow of information on each link, and the distribution of two payment systems, namely cash and credit payments. The supply chain performance in the eel culture industry obtained a performance value of 82.63 which indicates that the achievement of the company's supply chain performance is in the good category, and improvements need to be made especially on the deliver process performance indicators with a value of 2.70. Keywords: : glass eel, supply chain, eel, Cimandiri River